Turnover Theory at the Empirical Interface: Problems of Fit and Function - Steel, Robert P. (Academy of Management Review, 2002)
There are problems of fit between standard research practices in the domain of turnover research and evolutionary decisional processes like job search. I analyze this problem from methodological, empirical, and conceptual vantage points. Reanalysis of data suggests that the ability to accurately estimate employment opportunity is related to one's temporal positioning within the turnover process. Using cybernetic decision theory as a point of departure, I propose a model conceptualizing employment search processes as a series of decision stages.